2021
DOI: 10.3390/ijerph18105314
|View full text |Cite
|
Sign up to set email alerts
|

When Natural Hazards Intersect with Public Health: A Preliminary Exploration of the Impact of Bushfires and the COVID-19 Pandemic on Australian Coastal Drowning Fatalities

Abstract: Natural hazards combined with the COVID-19 pandemic have had significant global impacts to the community and the environment. This study explores the impact of the Australian 2019/20 bushfires followed by the COVID-19 pandemic on unintentional coastal drowning fatalities. Fatality data were collated using triangulation methodology. Percentage change in coastal drowning fatalities between 2019/20 financial year (FY) and the 15FY annual average (2004/5–2018/19) were calculated for the dominant bushfire period (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Powerboat sales reached a 13-year high in 2020 in the United States, increasing 12% over the previous year ( National Marine Manufacturers Association, 2020 ). Similar increases in boating-related drowning and boating sales contributed to increased drowning in Australia in 2020 ( Lawes et al, 2021 ). In one study, young adults in Canada identified outdoor activities, including spending time at the beach, as an important coping mechanism during the COVID-19 pandemic ( Ferguson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Powerboat sales reached a 13-year high in 2020 in the United States, increasing 12% over the previous year ( National Marine Manufacturers Association, 2020 ). Similar increases in boating-related drowning and boating sales contributed to increased drowning in Australia in 2020 ( Lawes et al, 2021 ). In one study, young adults in Canada identified outdoor activities, including spending time at the beach, as an important coping mechanism during the COVID-19 pandemic ( Ferguson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 95%
“…One study conducted in Guangdong, China found drowning deaths had decreased by 35% during the COVID-19 pandemic (January–June 2020) compared to the same timeframe in the prior year ( Zheng et al, 2021 ). Another study examined unintentional coastal drowning fatalities in Australia and found the risk of drowning was 1.75 times higher during the COVID-19 restriction period (March – June 2020) compared to the previous 15 years on average ( Lawes, Strasiotto, Daw, & Peden, 2021 ). Specifically, drowning while boating or using personal watercraft had the largest increase (88%; Lawes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound hazards that combined natural hazards and the COVID-19 pandemic have had major impacts on the community and the environment, and consequently increased the virus spread [1,2]. In such multiple-hazard crises, governments and other responding agents are required to make complex, highly compromised, hierarchical decisions aimed to balance COVID-19 risks and protocols with disaster response and recovery operations.…”
Section: Introductionmentioning
confidence: 99%